Analisis Komposisi Minyak Karo di Desa Naman Kecamatan Naman Teran - Ginting, Khairunnisa Br (Hijaz: Jurnal Ilmu-Ilmu Keislaman, 2022)
Karo oil is a traditional medicine that has been passed down from generation to generation and is still used today in traditional medicine. This study aims to determine the composition contained in karo oil in Naman Village, Naman Teran District. This research will explain the ingredients, method of preparation, composition and types of karo oil in the Traditional Medicine system. This research is a descriptive study using a qualitative approach. This study used observation techniques, in-depth interviews, informant approaches and analysis to obtain the required data. The informants in this study were the owners of Karo Oil in Naman Village, Naman Teran District, managers and consumers who use the Karo Oil they produce. The results of this study indicate that there are 5 types of karo oil in Naman village, Naman Teran subdistrict, namely butet naman karo oil, harvy karo biring oil, green oil, monitor lizard oil and kem-kem oil. The composition of the organs used in the manufacture of karo oil are roots, stems, rhizomes, seeds, tubers and leaves. The process of making karo oil is that first all the ingredients are cleaned then the ingredients are put into the container. After that, it is cooked and stirred evenly until the color changes to black or brown, with a cooking time of 5-8 hours